Urgensi Pengaturan Pertanggungjawaban Pidana atas Tindakan yang Dilakukan oleh Autonomous Artificial Intelligence - Yudhistira, Ade Rangga Permana; Zakaria, Alfons (RechtJiva, 2026)
The rapid advancement of Autonomous Artificial Intelligence (Autonomous AI) has introduced significant legal challenges, particularly concerning criminal liability for independent AI actions without human intervention. In Indonesia, this issue is exacerbated by regulatory gaps within the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), which currently do not accommodate autonomous non-human entities. Utilizing a normative juridical research method with statutory, conceptual, and comparative approaches specifically referencing the EU AI Act this study highlights a critical void in applying the principles of mens rea and actus reus to AI systems. Consequently, this research recommends a comprehensive legal reform of the KUHP and UU ITE, proposing a risk-based liability model, mandatory human oversight for high-risk systems, and algorithmic transparency to ensure legal certainty and foster safe, ethical AI innovation in Indonesia.